Factors determinant of patients’ satisfaction towards health tourism in Malaysia - Haque, A. K. M. Ahasanul; , Farzana Yasmin; Anwar, Naila (Research Publishing Academy (RPA), 2018)
Health tourism is a new form of tourism which is increasingly getting popularity around the world. Recently, Malaysia has become a favourite destination for health tourism. In order for Malaysia to attract more health tourists, it is imperative to determine the crucial factors concerning patients’ satisfaction. This research has been designed to analyze the factors that may affect patients’ satisfaction with health tourism, particularly in the context of Malaysia. Specifically, the study tries to examine the relationship between patients’ satisfaction and cost, service quality, motivation, destination image and perceived value. With the aim of achieving these objectives, this study has developed a framework on the basis of prior studies. In addition, data has been collected via self-structured questionnaire from patients visiting Malaysia, specifically Kuala Lumpur for the purpose of health tourism. The collected data from the respective respondents were analyzed through Statistical Package for Social Sciences (SPSS). SPSS has been used in order to assess the demographic profile of the respondents, run exploratory factor analysis and multiple regression analysis. The findings of the study demonstrated that cost, service quality and motivation are significantly related to satisfaction toward health tourism, whereas destination image and perceived value are not.